A review of the hydrothermal carbonization of biomass waste for hydrochar formation: Process conditions, fundamentals, and physicochemical properties. (July 2018) - Wang, Tengfei; Zhai, Yunbo; Zhu, Yun; Li, Caiting; Zeng, Guangming
Abstract: Hydrothermal carbonization (HTC) is a thermochemical conversion technique which is attractive due to its ability to transform wet biomass into energy and chemicals without predrying. The solid product, known as hydrochar, has received attention because of its ability to prepare precursors of activated carbon in wastewater pollution remediation, soil remediation applications, solid fuels, and other carbonaceous materials. Besides the generally lignocellulose biomass used as sustainable feedstock, HTC has been applied to a wide range of derived waste, including sewage sludge, algae, and municipal solid waste to solve practical problems and generate desirable carbonaceous products. This review presented the critical hydrothermal parameters of HTC, including temperature, residence time, heating rate, reactant concentration, and aqueous quality. The chemical reaction mechanisms involved in the formation of hydrochar derived from single components and representative feedstock, lignocellulose, and sludge termed as N-free and N-rich biomass, were elucidated and summarized to better understand the hydrochar formation process. Specifically, hydrochar physicochemical characteristics such as surface chemistry and structure were investigated. Current knowledge gaps, and new perspectives with corresponding recommendations were provided to further exploit the great potential of the HTC technique and more practical applications for hydrochar in the future. Highlights: Hydrothermal carbonization of biomass waste receives great deal attention. Hydrothermal conditions during HTC process are critical to hydrochar production. The chemical reaction mechanisms involved in hydrochar formation are reviewed. Hydrochar physicochemical characteristics from biomass waste are summarized.